Design of SPWM Controller for Power Assembly Test - LIU Min; LU Shenwen; ZHOU Yongcheng; CHEN Zhengwen; PAN Huan; PENG Peng (Kongzhi Yu Xinxi Jishu)
In order to solve the problems of limited interface and complex code in DSP controller, it presented a design method of SPWM(sinusoidal pulse width modulation) controller based on“DSP Builder+ FPGA” for power assembly test. As for the disadvantages of FPGA, such as difficulties of resource utilization control and long compiling time, the application of Quartus software resource analysis tool is performed to determine the chip resources, and the key parameters are open on the PC terminal to solve these problems. The proposed method has the advantages such as simple debugging and short development cycle. Finally, the method was applied to the power cycles test, and experimental results proved the feasibility of the method.